Comparison of continuous infusion and bolus administration of tramadol in postoperative children - Jeanne-Roos Tikoalu; Darlan Darwis; Bambang Madiyono (Paediatrica Indonesiana, 2003)
Objective To appraise the efficacy of tramadol therapy given bycontinuous infusion and bolus in handling child’s postoperative painthat is mostly inadequate.Methods This was a randomized, single-blinded clinical trial withparallel design. The study was done in the operation room, recov-ery room, pediatric intensive care unit, pediatric surgery, and pedi-atric ward of Cipto Mangunkusumo Hospital, Jakarta, Indonesia.There were sixty patients, 1-12 year-old, with elective operationbetween January and April 2002. Both groups received bolus of2mg/kg tramadol as an initial dose. Twenty-nine subjects receivedcontinuous infusion of 0.22 mg/kg/h tramadol in 15 minutes after-wards. The other 31 subjects received the same boluses for every6 hours. Before each tramadol administration, evaluation was doneby observer using objective pain scale (OPS) and evaluation sheetthat had been tested before the study. The study was done within24 hours post surgery.Results In the first 6 postoperative hours, mean total dose givenby continuous infusion was significantly greater than that given bybolus (p=0.006). On the contrary, mean total dose given within 24hours by continuous infusion was significantly less than that givenby bolus (p=0.037). All subjects showed OPS result of 36 in 0 minute.After that, the result decreased, except in 9 subjects it was still >6in the 15 th minute. Vomiting was the commonest side effect.Conclusion Continuous infusion of tramadol within 24 hours canbe recommended as an analgesic in postoperative children